MANAJEMEN BRANDING PESANTREN MELALUI PROGRAM QITAM DI PONDOK PESANTREN AL-ANSHOR - Adiba Salwa; Mohamad Joko Susilo (Jurnal Manajemen Pendidikan, 2026)
This study aims to explore pesantren branding management through the QITAM Program as a strategy for institutional identity formation at Al-Anshor Islamic Boarding School since its early stages of development. The focus of the study is on how this flagship program was designed, positioned, and integrated in an effort to build the image of the pesantren in the community. This study uses a qualitative descriptive approach with a case study method, where the descriptive approach is used to describe and explain the phenomenon of branding management systematically based on interview data, documents, and relevant scientific sources. The results show that Islamic boarding school branding management through the QITAM Program is a well-planned, relevant, and effective strategy in building the identity of Islamic boarding schools. The QITAM Program is positioned as a leading identity that integrates four strategic dimensions, namely Qur'anic, Scientific, Turats, and Modern, so that it is able to represent the vision, values, and distinctive character of the Al-Anshor Islamic Boarding School consistently and easily recognizable by the public.